A complex mathematical model of a single-span mobile pendulum-type ropeway based on airmobile rope units - Lagerev A.V.; Lagerev I.A. (Naučno-Tehničeskij Vestnik Brânskogo Gosudarstvennogo Universiteta)
Single-span mobile ropeways on the basis of two airmobile rope units connected by a single carrying-traction rope system currently represent the newest type of aerial ropeways designed for pre-property use in difficult natural conditions in the absence of the necessary ground transport infrastructure. The article considers the problem of developing a complex mathematical model of a single-span mobile pendulum-type ropeway based on airmobile rope units, which can be considered as a basis for further research on the creation of an integral scientifically based theory of this type of transporting equipment. The methodological principles of creating the specified mathematical model are formu-lated, its structure is proposed and a brief description of the internal subsystems of the model is given.